PEMBELAJARAN KREA TIF•PRODUKTIF UNTUK MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS DAN KREATIF BAGI MAHASISWA - Pratiwi Pujiastuti (Dinamika Pendidikan, 2009)
A  creative-productive   learning is  one learning model emphasizing the students to be active or a student-centered   learning. This learning model challenge the students in developing creativity to produce a product derived from  their understanding on  the  concept  studied. The  learning climate  is  interesting, challenging, enjoyable and meaningful to the students. The   creative-productive learning  model   includes:  active   students' involvement,  both intellectual  and emotional,  through exploring  the concept to be studied. the students construct  the concept studied by themselves, and the students are responsible for completing  the task. The students active in attending the learning process is  the important requirement in developing the critical and creative thinking skill: suchskill needs to be trialed to the students through the creative-producttve learning model. Many concepts are taught using the creative-productive  learning model; the lecturer is expected to try this learning model. Keywords: The creative-productive  learning model, critical-creative thinking skill